25 years of CBNRM in Namibia: A retrospective on accomplishments, contestation and contemporary challenges (Journal of Namibian Studies : History Politics Culture, 2015)
Namibia’s conservancy programme was launched officially in 1998 and, by 2005, Community-Based Natural Resource Management (CBNRM) was firmly established in Namibia’s national development plans. The uptake of the conservancy model by rural residents all over the country and the growth in CBNRM earnings, have been extraordinarily rapid. The country’s CBNRM policies have been lauded as the most progressive of their kind in southern Africa. Given that the evolution of CBNRM in Namibia is linked to the broader historical processes of colonisation and apartheid, and the highly skewed land distribution which those systems engendered, the recurring themes that arise in evaluating CBNRM are no surprise: they hinge on institutions, authority, heterogeneous interests within ‘communities’, and the un¬certainty of rural land tenure. This article examines both CBNRM’s successes as well as the academic criticism it generates, and, importantly, offers an assessment of key challenges facing Namibian CBNRM today, including the sustainable support of the rapid growth of conservancies, changes in the environmental donor landscape, and the rise of an international anti-hunting lobby. Our intention is to provide perspectives from both an academic and a practitioner’s point of view.